Perkawinan Sebagai HAM - Amin Ash Shabah, Musyaffa (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
This study analyzes same-sex marriage and interfaith marriage in the perspective of HumanRights and Islamic Law. This research is a library research using the juridical-normative approachand descriptive analysis data. The results of the study show that same-sex marriage by nature hasagainst the nature of human life that is born to establish mental and biological bonds between theopposite sex, namely between men and women. The Positive Legal Review emphasizes that in theMarriage Law, it is stated that marriage is a physical and spiritual bond between a man and a womanto form a family or household and to carry on offspring and aim at upholding religious teachingsand carrying out customs. On the other hand, Islamic religious law also explicitly prohibits same-sexmarriage. As for the relation to interfaith marriage, if it is legalized, it is a violation of the constitution.Article 29 of the 1945 Constitution states that the State is based on the One Godhead (paragraph 1).The state guarantees the freedom of every resident to embrace his own religion and worship accordingto his religion and belief (verse 2). This article clearly states that the State guarantees every citizento practice his religious teachings. One form of freedom of religious worship is manifested in theimplementation of marriage. Religion regulates the procedures for marriage, including what is allowedand not done. Six religions recognized in Indonesia reject interfaith marriage. The legalization ofinterfaith marriage means that the government does not respect the prevailing rules in religion.